Lyme disease and the pursuit of a clinical cure - Adkison, Heather; Embers, Monica E. (Frontiers in Medicine, 2023)
Lyme disease, caused by the spirochete Borrelia burgdorferi, is the most common vector-borne illness in the United States. Many aspects of the disease are still topics of controversy within the scientific and medical communities. One particular point of debate is the etiology behind antibiotic treatment failure of a significant portion (10–30%) of Lyme disease patients. The condition in which patients with Lyme disease continue to experience a variety of symptoms months to years after the recommended antibiotic treatment is most recently referred to in the literature as post treatment Lyme disease syndrome (PTLDS) or just simply post treatment Lyme disease (PTLD). The most commonly proposed mechanisms behind treatment failure include host autoimmune responses, long-term sequelae from the initial Borrelia infection, and persistence of the spirochete. The aims of this review will focus on the in vitro, in vivo, and clinical evidence that either validates or challenges these mechanisms, particularly with regard to the role of the immune response in disease and resolution of the infection. Next generation treatments and research into identifying biomarkers to predict treatment responses and outcomes for Lyme disease patients are also discussed. It is essential that definitions and guidelines for Lyme disease evolve with the research to translate diagnostic and therapeutic advances to patient care.